On the Possible Stability of Tetraneutron and Hexaneutron - Anagnostatos, G. S. (HNPS Advances in Nuclear Physics, 2020)
A specific cluster approach, in the framework of the Isomorphic Shell Model, is employed to examine the possible stability of 2n, 4n, and 6n. According to this study 2n is definitely unstable, while 4n and 6n could be stable or, at least, exhibit a low-lying resonance. Better knowledge of the strength of the neutron-neutron force is highly desirable.